Dossier I: Cooperación policial:Laagencia europea de fronteras y costas (frontex) - Gutiérrez Vera, Jesús (Quadernos de criminología, 2022)
Frontex, the European Border and Coast Guard Agency, was created in 2004 to help EU Member States and Schengen Associated Countries protect the external borders of the EU's free movement area. As an EU agency, Frontex is financed from the EU budget and from contributions from the Schengen associated countries.